E-Commerce Adoption, Social Media Marketing Strategy and MSME Performance : The Mediating Role of Business Sustainability in the Creative Industry - Diana Ambarwati; Agus Hermawan; Nuril Aulia Munawaroh (Cita konsultindo, 2024)
MSMEs must employ the appropriate technology and comprehend the proper online marketing strategy to use social media and e-commerce efficiently. The creative industry of CV. Putra Wijaya has completed this task the Adia brand. This study attempts to find out if business sustainability predictions have a direct impact on MSME performance, e-commerce adoption dan social media marketing strategy predictions have a direct impact on business sustainability and MSME performance, business sustainability in indirectly mediating e-commerce adoption and social media marketing strategy on MSME performance CV.Putra Wijaya. This study employs a quantitative methodology with a population and sample of 170 customers who bought Adia brand products from February to March 2024. In collecting data, this research used a questionnaire and analyzed using SmartPLS 3. The results of this research show that business sustainability has a direct and positive effect on MSME performance, e-commerce adoption does not have a direct and positive effect on business sustainability, e-commerce adoption also does not have a direct and negative effect on MSME performance, but social media marketing strategy has adirect and positive effect on business sustainability and MSME performance. Business sustainability cannot mediate e-commerce adoption indirectly and positively on MSME performance, but business sustainability can mediate social media marketing strategy indirectly and positively on MSME performance at CV. Putra Wijaya.